Preliminary Evaluation of Some Elicited Apple Genotypes Candidate as Cultivars Using Morphological and Molecular Markers - Muzher, Bayan; Al-Halabi, Ola (International Journal of Environment, 2016)
Preliminary evaluation of 5 apple genotypes produced by seed selection in the germplasm of seed rootstocks in Sweida- Syria was carried out between 2005 and 2012, to study date of full flowering, maturity time, morphological characters of tree, shoots, leaves, flowers, and fruits, including chemical analysis. On the other hand, yield efficiency, fruit storability and the susceptibility to pests and physiological disorders were evaluated. Molecular characterization was achieved by using 8 pairs of SSR primers for the 5th genotypes in comparison with the two main commercial cultivars "Golden Delicious" and "Starking Delicious" to determine the genetic relationship between the studied genotypes and cultivars. The results divided the studied genotypes depending on the time of ripening into three groups: early, intermediate and late genotypes. All studied genotypes gave efficient and regular yield, and showed fixable fruit shape and size with variable storability due to maturity time. Molecular characterization reveled the ability of SSR technique to determine the genetic variation between the studied genotypes, the 8 primer pairs produced 22 alleles, 21 of them were polymorphic (95.45%). Cluster analysis divided the studied genotypes into 2 clusters, the first cluster included the two commercial cultivars Starking delicious and Golden delicious with one genotypes, while the second cluster contained the four remaining genotypes. Finally, the studied genotypes revealed high desired quantitative and qualitative traits, which assess to distribute these genotypes as new cultivars, and SSR technique was able to identify and revealed the genetic distance between the studied genotypes and commercial cultivars.INTERNATIONAL JOURNAL OF ENVIRONMENTVolume-5, Issue-2, March-May 2016, page: 98-109